A novel perspective on bone tumors: advances in organoid research - Ma, Zebing; Liu, Yibing; Chen, Rui; Fan, Huayu; Kong, Liang; Cao, Xiangyang (Frontiers in Pharmacology, 2025)
Bone tumor organoids are three-dimensional cell culture models derived from patient tissues or cells, capable of highly replicating the growth patterns and cell interactions of bone tumors in vitro. Current treatments for bone tumors are hindered by challenges such as drug resistance, recurrence, and metastasis. Organoids enhance the physiological relevance of bone tumor models, thereby improving treatment precision and overcoming the limitations of current therapeutic approaches. Organoid technology has made preliminary applications in bone tumor research, including primary bone tumors, metastatic bone tumors, and bone marrow-derived bone tumors. This review will explore the establishment of bone tumor organoids, summarize their applications and prospects in various bone tumor diseases, and discuss their integration with emerging technologies. Additionally, the limitations and future directions of bone tumor organoid research will be discussed. In the future, bone tumor organoids are expected to promote the further development of precision medicine.